Effect of ZnSO4 Fertilizer Application on Growth and Essential Oil Content of Green Betel Plant (Piper betle L.) - Sinar Suryawati; Wahyu Nur Laili; Eko Murniyanto (Future Science, 2021)
Green betel (Piper bettle L.) is a medical plant that contains essential oil and is widely used as one of the key ingredients of traditional herbal called jamu. One of the particular micronutrients that play an important role in an enzyme activator is Zinc mineral (Zn). This research was aimed to discover the most effective doses of ZnSO4 fertilizer on growth parameters and essential oil production of green betel cultivated on red mediterranean soils in Bangkalan Madura, at ± 5 altitudes. This experiment was arranged as a single factor experiment in a completely randomized design with four replications. There were six levels of treatment namely Z0 (without ZnSO4), Z1(0,2 g/plant), Z2 (0.4 g/plant), Z3 (0.6/plant), Z4 (0.8 g/plant), Z5 (1 g/plant). Data collected from this experiment were analyzed using analysis of variance (ANOVA), followed by Duncan multiple ranged test (DMRT) ?? 5%. The results showed that the application of ZnSO4 fertilizer significantly affects vine height, number of leaves, number of branches, number of nodes, plant total dry weight, and essential oil content. Doses 0.6 g/plant of ZnSO4 was the best treatment compared to other doses applied in this research which increased the essential production of green betel up to 36.6% (1.405% w/w) compared to the control (without ZnSO4 application).